Optimasi Penjadwalan Produksi Sanjai Menggunakan Algoritma Campbell Dudek Smith - Sari, Lusi Febrina; Helma, Helma (Journal of Mathematics UNP, 2023)
scheduling is an important component in planning deals with time management for all activities required in the process of making goods or services. Production scheduling is a tool used to determine the time period used in each working day during the production process. through the use of the Campbell Dudek Smith algorithm, this research aims to obtain satisfactory production result, namely achieving the minimum total work time so as to solve the the problem of product delivery delays at the Kerupuk Sanjai Nitta business. The Campbell Dudek Smith algorithm can determine the best scheduling order by prioritizing jobs with the least production processing time in the production process. This algorithm, which is an extension of Johnson’s algorithm, produces  iterations for alternative work schedule sequences. The results show that the best result optimal scheduling is obtained from the fifth iteration with takes a total time of  hours, so that Sanjai Nitta’s business can complete the production process earlier and save  hours of work time.